Factors Associated with Binge Drinking during the Transition into Adulthood: Exploring Associations Within Two Distinct Young Adult Age Ranges. (August 2020) - Leech, Tamara GJ; Jacobs, Sarah; Watson, Dennis
Background: Binge drinking among young adults aged 18-21 years has declined over the past decade, but binge drinking rates among people 22-25 years old have remained largely the same. This steady trend in later years represents a departure from the traditional course of maturing out of risky alcohol use, perhaps because young adults are delaying the transition into adulthood. Aims: This paper explores the relationship between binge drinking and aspects of the transition into adulthood that could inform interventions targeting these two distinct groups of young adults. Methods: We use survey data on 1, 081 young adults aged 18-25 living in 10 Indiana counties. Our dataset is unique because it contains both college-attending and non-college attending young adults. We ran weighted logistic regressions to determine the association between college enrollment, living situation, roles common in adulthood, and stressors common during the transition to adulthood (e.g., relationships, economic conditions, job stability) and binge drinking. Results: Our data indicate that different factors are associated with binge drinking based on whether subjects who are in the earlier (18-21 years old) or later (22-25 years old) years of young adulthood. For example, within the 18-21 years old group, college enrollment is associated with higher rates of binge drinking, but it is not associated with increased binge drinking in the older age group. The type of stress related to binge drinking also varies by age group. Conclusion: Our results emphasize the need to disaggregate "young adulthood" into two separate periods when defining target populations and settings for binge drinking interventions.